Positivity-Preserving Piecewise Rational Cubic Interpolation (MATEMATIKA, 2006)
A piecewise rational cubic spline [5] has been used to visualize the positive data in its natural form. The spline representation is interpolatory and applicable to the scalar valued data. The shape parameters in the description of a rational cubic have been constrained in such a way that they preserve the shape of the positive data in the view of positive curve. As far as visual smoothness is concerned, the curve scheme under discussion is $C^1.$ Keywords: Data visualization; interpolation; rational cubic.